Digital heat transfer paper with low rejection rate and preparation method

By combining surface coating glue solution and slurry application glue solution, using raw materials such as silica, carboxymethylcellulose, the problems of yellowing and high waste rate of digital thermal transfer paper are solved, and a higher rate of production has been achieved The water resistance and glossiness significantly reduce the waste rate.

CN119266016AActive Publication Date: 2025-01-07WUZHOU SPECIAL PAPER GRP CO LTD

Patent Information

Application Number
CN202411479994.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-07
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Existing digital thermal transfer papers are prone to yellowing after being stored for a long time, with high waste rate and insufficient water resistance, which affects its stability and gloss.

Method used

By combining surface coating adhesive liquid and slurry application liquid, high strength and resistance are formed by mixing silica, sodium carboxymethylcellulose, cationic starch, wet strength agent, talc powder and modified adhesive agent. Paper with abrasive and glossiness reduces waste rate and improves water resistance.

Benefits of technology

The waste rate of digital thermal transfer paper is significantly reduced, its water resistance and gloss is improved, the paper remains stable after long storage, and it exhibits higher tensile strength and flatness during printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097097170000061
    Figure BDA0005097097170000061
  • Figure BDA0005097097170000091
    Figure BDA0005097097170000091
Patent Text Reader

Abstract

The invention discloses digital heat transfer paper with low rejection rate and a preparation method thereof. The digital heat transfer paper is prepared by the following steps: firstly, preparing a surface coating glue solution, then carrying out pulping, pulping and proportioning on the pulp, and carrying out a plurality of processes of forming on a net, carrying out surface sizing and coating, thereby finally obtaining the digital heat transfer paper. The sizing agent is modified by using the grafting agent to obtain the modified sizing agent, and then the modified sizing agent is applied to the digital heat transfer paper, so that compared with the prior art, the digital heat transfer paper prepared by the invention has the advantages of good glossiness, relatively good hydrophobicity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of special paper production, and in particular to digital thermal transfer paper with low waste rate and a preparation method thereof. Background Art

[0002] Digital thermal transfer technology is a process that prints images or texts on special transfer paper through digital devices (such as inkjet printers, laser printers, etc.), and then transfers the images to other materials (such as cloth, ceramics, metals, plastics, etc.) by heat pressing or thermal sublimation. This technology not only achieves high-precision and high-resolution image transfer, but also retains the color and details of the original image, greatly enriching the selection and application range of printing materials.

[0003] As the core carrier of this technology, digital thermal transfer paper has a series of unique properties and characteristics. First, it has good ink absorption and color reproduction, which can ensure that the printed image is bright and layered. Secondly, the surface of digital thermal transfer paper has been specially treated, which has excellent adhesion and wear resistance, making the transferred image not easy to fall off or fade. In addition, it also has good thermal stability and dimensional stability, which can maintain a stable shape and size during the thermal transfer process, ensuring the accuracy and consistency of the transfer effect.

[0004] With the continuous advancement of technology and the continuous expansion of the market, the performance and application of digital thermal transfer paper are also constantly innovating and developing. For example, some new digital thermal transfer papers have higher weather resistance and water resistance, and can keep the color bright and stable for a long time in outdoor environments; some digital thermal transfer papers with special textures and textures also provide users with more choices and personalized customization space.

[0005] CN106758536A discloses a method for producing light-coated digital thermal transfer paper, including the preparation of sizing solution in pulp, preparation of surface sizing solution, preparation of surface coating glue solution, pulp crushing, pulping-slurry preparation process, screen forming, surface sizing, and coating steps. The invention provides a method for producing light-coated digital thermal transfer paper with good ink compatibility, fast drying speed, high transfer rate, and no curling. The production method organically combines the production of coating with the production of base paper, and the production is completed in one go. However, the light-coated digital thermal transfer paper prepared by this method is prone to problems such as brittle paper and high scrap rate.

[0006] CN111636242A discloses a micro-coated sublimation thermal transfer paper and a preparation method thereof, comprising base paper and an ink-absorbing coating coated on the base paper. The coating used to prepare the ink-absorbing coating is recorded in parts by weight, and the raw materials include: 0.6-2 parts of polyepichlorohydrin-dimethylamine modified nano-silicon dioxide, 6-16 parts of acrylamide modified polyvinyl alcohol, 100-200 parts of water, and the coating amount of the coating is 3-5g / m2 . The invention modifies the binder and pigment in the coating, and uses the reaction between the binder and the pigment to connect the pigment and the binder through chemical bonds, so as to prevent the pigment from falling off from the binder when the coating is thin and affecting the absorption of ink; and the modified binder and pigment can not only accelerate the absorption of ink, but also fix the ink in the coating to prevent the ink from penetrating into the paper surface. However, the thermal transfer paper prepared by this method tends to turn yellow after being stored for a long time. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to reduce the scrap rate of digital thermal transfer paper, improve the water resistance of digital thermal transfer paper, make the digital thermal transfer paper after applying the glue liquid more stable and able to be placed for a longer time, and at the same time improve the glossiness of the paper.

[0008] To achieve the above object, the present invention provides a method for preparing digital thermal transfer paper with low waste rate, comprising the following steps:

[0009] Step 1, preparation of surface coating glue: 20-30 parts by weight of water, 1-5 parts by weight of silicon dioxide and 2-7 parts by weight of sodium carboxymethyl cellulose are mixed to obtain a surface coating glue;

[0010] Step 2, pulp crushing and beating: add 20-50 parts by weight of softwood pulp to 3-7 parts by weight of water, crush for 10-20 minutes, and then add 1-5 parts by weight of water to make a mixed pulp with a beating degree of 50-300SR;

[0011] Step 3, slurry preparation: 8-12 parts by weight of mixed slurry, 20-25 parts by weight of slurry sizing liquid, and 1-5 parts by weight of wet strength agent are mixed evenly to obtain a mixed slurry;

[0012] Step 4, forming on the screen: dilute 33-50 parts by weight of the mixed slurry with 2-10 parts of water, form on the screen, and add 0.3-1 parts by weight of cationic polyacrylamide and 2-6 parts by weight of talcum powder; add 4-8 parts by weight of silica sol in the low-concentration stabilizing box; add 5-15 parts by weight of modified sizing agent in the outlet pipe of the low-concentration stabilizing box, and then form on the screen, squeeze and dehydrate, and dry to obtain paper sheets;

[0013] Step 5, surface sizing and coating: the surface sizing liquid is applied to the front side of the paper sheet through a metering rod in a film transfer sizing machine, and the surface coating glue liquid prepared in step 1 is applied to the back side of the paper sheet through a metering rod in a film transfer sizing machine, and then dried through a heat exchanger, an oven and a drying cylinder, and then calendered, coiled and slit to form a finished product.

[0014] Preferably, the coating amount of the adhesive in step 1 is 2-10 g / m 2; Silica particle size is 2-10mm, pore volume is 1.5-3.0cm 3 / g.

[0015] Preferably, the preparation method of the surface sizing solution comprises the following steps: stirring and mixing 150-200 parts by weight of water and 10-20 parts by weight of cationic starch at 300-500 rpm for 10-20 min, heating to 85-90° C., and keeping warm for 15-20 min; adding 1-3 parts by weight of a styrene-containing lipid copolymer surface sizing agent at 85-90° C., stirring and mixing at 300-500 rpm for 10-30 min, controlling the temperature at 50-65° C. and keeping warm for 10-15 min, and then cooling to room temperature to obtain a surface sizing solution.

[0016] Preferably, the preparation method of the slurry sizing solution is: 100-150 parts by weight of water and 8-15 parts by weight of cationic starch are stirred and mixed at 300-500 rpm for 20-30 minutes, heated to 85-90°C, kept warm for 15-20 minutes, and then cooled to room temperature to obtain the slurry sizing solution.

[0017] Preferably, the preparation method of the modified sizing agent comprises the following steps, measured in parts by weight:

[0018] S1: Add 15-35 parts of N,N-dimethylformamide, 2-5 parts of sizing agent and 1-3 parts of sodium hydroxide, stir and mix at room temperature for 1-4 hours, then add 0.001-1 parts of 4-dimethylaminopyridine and 1-6 parts of grafting agent, keep stirring at 30-75°C for 2-5 hours;

[0019] S2: Filter the substance obtained in S1 to obtain a filter cake, wash it with a 70-90 wt% ethanol aqueous solution for 1-3 times, dry it at 50-65° C. for 1-4 hours, and cool it to room temperature to obtain a modified sizing agent.

[0020] Preferably, the sizing agent is any one of hydrogenated rosin glycerol ester, sodium alginate, and carboxymethyl chitosan.

[0021] Preferably, the grafting agent is any one of monomethyl malonate, 3-methoxy-2-methyl-3-oxopropionic acid, and 3-[(tert-butoxycarbonyl)sulfanyl]propionic acid.

[0022] More preferably, the grafting agent is 3-[(tert-butoxycarbonyl)sulfanyl]propionic acid.

[0023] Preferably, in step 5, the metering rod is 20-50S, the surface glue liquid is applied on the front side, the viscosity of which is 10-40mPa.s and the solid content is 8-15%; the glue liquid is applied on the back side, the viscosity of which is 350-500mPa.s and the solid content is 30-50%.

[0024] A digital thermal transfer paper with low waste rate is prepared by the method.

[0025] In this recipe, the ingredients and their functions are as follows:

[0026] Cationic starch mainly plays the role of sizing inside the pulp. It forms a thin film inside the pulp, which strengthens the bonding force between the fibers of the paper and improves the water resistance of the paper, thereby reducing the scrap rate.

[0027] Silicon dioxide mainly acts as a surface coating enhancer. By mixing it with sodium carboxymethyl cellulose in a certain proportion to prepare a coating glue and coating it on the back of the paper, silicon dioxide can significantly improve the surface strength and wear resistance of the paper.

[0028] Sodium carboxymethyl cellulose mainly plays the role of bonding and film-forming of the coating glue. It is mixed with silicon dioxide in a certain proportion to form the coating glue that is applied to the back of the paper. As a water-soluble high molecular polymer, sodium carboxymethyl cellulose has good bonding, film-forming and water-retaining properties, and can effectively enhance the strength and smoothness of the paper surface.

[0029] Wet strength agent: Wet strength agent mainly plays the role of enhancing the wet strength of paper. Wet strength agent can form chemical bonds or hydrogen bonds with paper fibers, thereby significantly improving the bonding force between fibers when the paper is wet, preventing the paper from breaking or deforming when subjected to external forces.

[0030] Cationic polyacrylamide mainly plays the role of retention and drainage. It can adsorb and bridge with fibers, fillers and other particles in the pulp to form larger floccules, thereby accelerating the discharge of water in the pulp, increasing the water filtration rate, and facilitating the rapid formation and dehydration of paper sheets.

[0031] As an inorganic filler, talcum powder can increase the whiteness and opacity of paper, making the printed image clearer and more vivid. Secondly, talcum powder has good smoothness and dispersibility, which can fill the gaps between paper fibers, improve the flatness of the paper surface, and help reduce ink penetration and diffusion during printing, thereby maintaining the fineness and edge clarity of the printed image.

[0032] The hydroxyl functional group in the sizing agent changes the molecular structure and properties of the sizing agent by chemically reacting with the carboxylic acid functional group in the grafting agent, such as esterification and cross-linking. This modification can make the modified sizing agent better bonded to the paper fiber, improve the sizing effect and water resistance of the paper, and also help improve other physical properties of the paper, such as strength, smoothness and glossiness.

[0033] The grafting agent mainly plays a key role in promoting chemical modification reactions and thus enhancing the performance of the sizing agent. Specifically, the grafting agent can undergo an esterification reaction with the active sites on the molecular chain of the sizing agent, introduce new functional groups or chain segments, and form a graft copolymer. The grafting agent contains sulfur atoms with a high refractive index, which can improve the glossiness of digital thermal transfer paper.

[0034] Beneficial effects of the present invention:

[0035] Compared with the prior art, a sulfur atom with a high refractive index and a reactive carboxylic anhydride or carboxylic acid grafting agent are used to undergo an esterification reaction with a sizing agent containing a hydroxyl functional group under wet conditions, thereby introducing sulfur atoms into the sizing agent to synthesize a modified sizing agent. The modified sizing agent can form ester bonds with the hydroxyl groups of paper fibers to improve the sizing performance of the paper. At the same time, the high refractive index of the sulfur atom improves the glossiness of the digital thermal transfer paper. DETAILED DESCRIPTION

[0036] Parameters for specific chemical substances used, sources.

[0037] Silica, 300 mesh.

[0038] Wet strength agent, model: Kymene TM 557, Brand: Solenis.

[0039] Cationic polyacrylamide, viscosity: 5800-6200 mPa·s, ionicity: 30%, source: Shanghai Aladdin Biochemical Technology Co., Ltd.

[0040] Silica sol, viscosity (25℃, ≤7.0mPa·s), diameter 10-20nm, Yantai Hengxin Chemical Technology Co., Ltd.

[0041] Cationic starch, model: CS-YLO3M, white powder, fineness (100 mesh sieve pass rate) ≥ 95%, viscosity (6%, 95℃, 1h, NDJ-8S) ≤ 2000mPa·s, degree of substitution 0.015-0.130, sourced from Guangdong Hongxin Biotechnology Co., Ltd.

[0042] Surface sizing agent containing styrene-ester copolymer, model: JH-611, viscosity (<50mPa·s(25℃)), pH value: 2-5, solid content (30%±1%), Qingzhou Jinhao New Materials Co., Ltd.

[0043] Talc, 400 mesh.

[0044] Coniferous wood pulp, using Asia Pacific Sembo's cultural paper pulp (BPW pulp), is bleached sulfate chemical pulp, with a whiteness of ≥89% and a dustiness of ≤2.0mm 2 / m 2 .

[0045] 3-methoxy-2-methyl-3-oxopropanoic acid, CAS No.: 111103-66-3.

[0046] 3-[(tert-Butyloxycarbonyl)sulfanyl]propanoic acid, Propanoic acid, 3-[[(1,1-dimethylethoxy)carbonyl]thio]-, CAS No.: 138754-12-8.

[0047]

[0048] Carboxymethyl chitosan, viscosity 10-100 mPa·s, carboxylation degree ≥80%, sourced from Shanghai Maokang Biotechnology Co., Ltd.

[0049] Hydrogenated rosin glycerol ester, product number: xyh001, Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd.

[0050] Starch is wheat starch, 300 mesh.

[0051] Example 1

[0052] A method for preparing digital thermal transfer paper with low waste rate comprises the following steps:

[0053] Step 1: Preparation of surface coating glue: add 1 kg of silicon dioxide and 4 kg of sodium carboxymethyl cellulose to 20 kg of water, start the disperser and mix at 3000 rpm for 30 min to obtain the surface coating glue, which is set aside;

[0054] Step 2: Pulp crushing and beating: Add 3 kg of water and 4 kg of softwood pulp to the hydraulic pulper, crush for 15 minutes, then add 2 kg of water to make a mixed pulp with a beating degree of 200 SR;

[0055] Step 3: Slurry preparation: Pump the mixed slurry prepared in step 2 into a batching tank, add 20 kg of slurry sizing liquid and 5 kg of wet strength agent into the batching tank and mix at 1000 rpm for 30 minutes to obtain slurry;

[0056] Step 4: Forming on the net: add 10kg water to the 50kg slurry prepared in step 3, screen and purify it through a slurry pump, a sand remover, and a pressure screen, and then enter a low-concentration stabilizing box for forming on the net; at the same time, add 0.3kg 0.03wt% cationic polyacrylamide and 4kg talcum powder at the inlet of the slurry pump; add 4kg silica sol to the low-concentration stabilizing box; add 8kg modified sizing agent to the outlet pipe of the low-concentration stabilizing box; after forming on the net, squeeze, dehydrate, and dry to obtain paper sheets;

[0057] Step 5: Surface sizing and coating: Apply the surface sizing liquid to the front of the paper sheet through a metering rod in a film transfer sizing machine, and apply the surface coating glue liquid to the back of the paper sheet through a 40s metering rod in a film transfer sizing machine, and then dry it through a heat converter, oven and drying cylinder, and then calender, coil and slit to make the finished product.

[0058] The preparation method of the slurry sizing solution is as follows: 100 kg of water and 8 kg of cationic starch are stirred and mixed at 300 rpm for 20 minutes, the temperature is raised to 90° C., the temperature is kept for 15 minutes, and then the temperature is cooled to 25° C. to obtain the slurry sizing solution.

[0059] The preparation method of the surface sizing solution is as follows: 200 kg of water and 20 kg of cationic starch are stirred and mixed at 300 rpm for 20 minutes, the temperature is raised to 90° C., and the temperature is kept for 15 minutes; 1 kg of a styrene-containing copolymer surface sizing agent is added at 90° C. and the mixture is stirred and mixed at 300 rpm for 30 minutes, the temperature is controlled at 65° C. and the mixture is kept for 10 minutes, and then the mixture is cooled to 25° C. to obtain the surface sizing solution.

[0060] Wherein, the preparation method of the modified sizing agent comprises the following steps:

[0061] S1: Add 20 kg N,N-dimethylformamide, 5 kg carboxymethyl chitosan and 2 kg sodium hydroxide, stir and mix at 25°C for 2 h, then add 3 kg 4-dimethylaminopyridine and 5 kg 3-[(tert-butoxycarbonyl)sulfanyl]propionic acid, and keep stirring at 65°C for 3 h;

[0062] S2: Filter the substance obtained in step 1 to obtain a filter cake, wash it twice with 75 wt % ethanol aqueous solution; bake it at 65° C. for 2 h, and cool it to room temperature to obtain a modified sizing agent.

[0063] Example 2

[0064] The difference between Example 2 of the present application and Example 1 is that the carboxymethyl chitosan in Example 1 is replaced by hydrogenated rosin glycerol ester.

[0065] Example 3

[0066] The difference between Example 3 of the present application and Example 1 is that the carboxymethyl chitosan in Example 1 is replaced by sodium alginate.

[0067] Example 4

[0068] The difference between Example 4 of the present application and Example 1 is that the 3-[(tert-butoxycarbonyl)sulfanyl]propionic acid in Example 1 is replaced by monomethyl malonate.

[0069] Example 5

[0070] The difference between Example 5 of the present application and Example 1 is that the 3-[(tert-butoxycarbonyl)sulfanyl]propionic acid in Example 1 is replaced by 3-methoxy-2-methyl-3-oxopropionic acid.

[0071] Comparative Example 1

[0072] The difference between Comparative Example 1 of the present application and Example 1 is that the carboxymethyl chitosan in Example 1 is replaced by starch.

[0073] Comparative Example 2

[0074] A method for preparing digital thermal transfer paper with low waste rate comprises the following steps:

[0075] Step 1: Preparation of surface coating glue: add 1 kg of silicon dioxide and 4 kg of sodium carboxymethyl cellulose to 20 kg of water, start the disperser and mix at 3000 rpm for 30 minutes to obtain the surface coating glue, which is set aside;

[0076] Step 2: Pulp crushing and beating: Add 3 kg of water and 4 kg of softwood pulp to the hydraulic pulper, crush for 15 minutes, then add 2 kg of water to make a mixed pulp with a beating degree of 200 SR;

[0077] Step 3: Slurry preparation: Pump the mixed slurry prepared in step 2 into the batching tank, add 20kg of slurry sizing liquid and 5kg of PPE wet strength agent into the batching tank and mix at 1000rpm for 30min to obtain slurry;

[0078] Step 4: Forming on the net: add 3kg water to the slurry prepared in step 3, screen and purify it through a slurry pump, a sand remover, and a pressure screen, and then enter the low-concentration stabilizing box to form on the net, and add 0.03% cationic polyacrylamide with a ton of paper consumption of 0.3kg and 30% talcum powder with a concentration of 150kg at the inlet of the slurry pump; add 4kg silica sol to the low-concentration stabilizing box; add 15kg carboxymethyl chitosan to the outlet pipe of the low-concentration stabilizing box, and then form on the net, squeeze and dehydrate, and dry to obtain paper sheets;

[0079] Step 5: Surface sizing and coating: Apply the surface sizing liquid to the front of the paper sheet through a metering rod in a film transfer sizing machine, and apply the surface coating glue liquid to the back of the paper sheet through a 40s metering rod in a film transfer sizing machine, and then dry it through a heat converter, oven and drying cylinder, and then calender, coil and slit to make the finished product.

[0080] The preparation method of the surface coating glue solution is as follows: 1 kg of silicon dioxide and 4 kg of sodium carboxymethyl cellulose are added to 20 kg of water, and a disperser is started to mix at 3000 rpm for 30 minutes to obtain the surface coating glue solution.

[0081] The preparation method of the surface sizing solution is as follows: add 200 kg of water and 20 kg of cationic starch, stir at 300 rpm for 20 min, heat to 90° C., keep warm for 15 min, mix 1 kg of styrene-containing lipid copolymer surface sizing agent at 300 rpm for 30 min, control the temperature at 65° C. and keep warm for use, to obtain the surface sizing solution.

[0082] Test Example 1

[0083] The coating hydrophobicity (g / ㎡) is tested according to GB / T 1540-2002 "Determination of water absorption of paper and paperboard (Cobber method)". The test results are shown in Table 1:

[0084] Table 1: Test of coating hydrophobic effect

[0085]

[0086]

[0087] Test Example 2

[0088] The paper glossiness was tested according to GB / T8941-2013 "Determination of specular glossiness of paper and paperboard". The test results are shown in Table 2:

[0089] Table 2 Paper gloss test

[0090] Experimental groups Glossiness / % Example 1 57.5 Example 2 50.2 Example 3 48.9 Example 4 49.5 Example 5 47.8 Comparative Example 1 38.7 Comparative Example 2 40.6

[0091] Through the test data results in the tables of Examples 1-5 and Comparative Examples 1-2, it can be found that the glossiness and hydrophobic effect of the digital thermal transfer paper prepared in Example 1 are the best.

[0092] The test principle of the CB method is based on measuring the water absorption of paper and paperboard surfaces under a certain pressure within a certain period of time. Specifically, a circular sample is placed in the ring fixture of the CB absorbency tester, and an absorbent pad (usually made of qualitative filter paper or other materials with good water absorption) is placed above the sample. Then, by applying a certain pressure, water is absorbed by the sample through the absorbent pad within a specified time. Finally, the CB absorbency value is calculated based on the amount of water absorbed by the sample.

[0093] Comparing the table data in Examples 1-3 and Comparative Example 2, it is found that the digital thermal transfer paper prepared in Example 1 has a better hydrophobic effect, which may be due to the use of different grafting agents. Since the fluidity and transparency of the sizing agent after gelatinization are not ideal, and it is easy to become turbid and form a gel after cooling, it is generally not directly used as a surface sizing agent, but the hydroxyl functional group contained in the sizing agent can be esterified with the carboxylic acid functional group contained in the grafting agent, so that other functional groups contained in the grafting agent are introduced into the sizing agent to obtain a modified sizing agent, which is then applied to the digital thermal transfer paper, which is beneficial to improve the tensile strength and folding resistance of the paper. The hydroxyl groups on the surface of the sizing agent are the reason for its good hydrophilicity. After modification by the grafting agent, the hydroxyl groups are converted into hydrophobic ester groups, so the hydrophobicity is better. By comparing the test data in Example 1 and Comparative Example 2, it can be found that no grafting agent is added in Comparative Example 2, and the sizing agent is not modified to introduce hydrophobic groups, thereby making the prepared modified sizing agent have a worse hydrophobic effect.

[0094] Comparing the tabular data of Example 1, Example 4 and Example 5, it is found that the digital thermal transfer paper prepared in Example 1 has the best gloss. This is mainly due to the sulfur element in 3-[(tert-butoxycarbonyl)sulfanyl]propionic acid. The sulfur atom has a high refractive index, and after grafting, it can significantly enhance the reflection of light on the surface of the paper, so that the gloss is significantly improved. At the same time, the carboxylic anhydride functional group in the grafting agent reacts with the hydroxyl group in the sizing agent to form a stable covalent bond, which enhances the binding force between the sizing agent and the paper fiber, further improves the flatness of the paper surface, and thus enhances the gloss. In addition, the hydrophobicity brought by the alkoxy and sulfur groups in the grafting agent reduces the interference of moisture on the surface, making the paper surface smoother and more uniform, and indirectly enhancing the gloss performance. In contrast, Examples 4 and 5 only contain carboxylic anhydride functional groups and lack sulfur atoms, so the paper prepared therefrom performs poorly in gloss. .

[0095] In summary, the present invention achieves a low scrap rate through multiple key technical steps. First, a modified sizing agent is used, and the sizing agent reacts chemically with the carboxylic acid functional group in the grafting agent to form a modified sizing agent, which enhances the sizing effect of the paper and makes the paper have better water resistance and strength. Secondly, the silica in the coating glue is mixed with sodium carboxymethyl cellulose to enhance the strength and wear resistance of the paper surface and reduce the damage of the paper during processing. The application of wet strength agent further improves the wet strength of the paper, ensures that the paper is not easy to break or deform in a wet state, and reduces the scrap caused by humidity changes. In addition, by adding talcum powder and cationic polyacrylamide during the molding process, the flatness and surface hydrophobicity of the paper are enhanced, the stability of the paper during the printing process is guaranteed, and the generation of scrap is reduced. Combining these technical means, the present invention greatly improves the quality stability of digital thermal transfer paper and significantly reduces the scrap rate in the production process.

Claims

1. A method for preparing digital thermal transfer paper with low waste rate, characterized in that: The steps include: Step 1, preparation of surface coating glue: 20-30 parts by weight of water, 1-5 parts by weight of silicon dioxide and 2-7 parts by weight of sodium carboxymethyl cellulose are mixed to obtain a surface coating glue; Step 2, pulp crushing and beating: add 20-50 parts by weight of softwood pulp to 3-7 parts by weight of water, crush for 10-20 minutes, and then add 1-5 parts by weight of water to make a mixed pulp with a beating degree of 50-300SR; Step 3, slurry preparation: 8-12 parts by weight of mixed slurry, 20-25 parts by weight of slurry sizing liquid, and 1-5 parts by weight of wet strength agent are mixed evenly to obtain a mixed slurry; Step 4, forming on the screen: dilute 33-50 parts by weight of the mixed slurry with 2-10 parts of water, form on the screen, and add 0.3-1 parts by weight of cationic polyacrylamide and 2-6 parts by weight of talcum powder; add 4-8 parts by weight of silica sol in the low-concentration stabilizing box; add 5-15 parts by weight of modified sizing agent in the outlet pipe of the low-concentration stabilizing box, and then form on the screen, squeeze and dehydrate, and dry to obtain paper sheets; Step 5, surface sizing and coating: the surface sizing liquid is applied to the front side of the paper sheet through a metering rod in a film transfer sizing machine, and the surface coating glue liquid prepared in step 1 is applied to the back side of the paper sheet through a metering rod in a film transfer sizing machine, and then dried through a heat exchanger, an oven and a drying cylinder, and then calendered, coiled and slit to form a finished product.

2. The method for preparing digital thermal transfer paper with low waste rate as claimed in claim 1, characterized in that: The coating amount of the adhesive in step 1 is 2-10 g / m 2 ; Silica particle size is 2-10mm, pore volume is 1.5-3.0cm 3 / g.

3. The method for preparing digital thermal transfer paper with low waste rate as claimed in claim 1, characterized in that: The preparation method of the surface sizing solution comprises the following steps: stirring and mixing 150-200 parts by weight of water and 10-20 parts by weight of cationic starch at 300-500 rpm for 10-20 minutes, heating to 85-90° C., and keeping the temperature for 15-20 minutes; adding 1-3 parts by weight of a styrene-containing lipid copolymer surface sizing agent at 85-90° C., stirring and mixing at 300-500 rpm for 10-30 minutes, controlling the temperature at 50-65° C. and keeping the temperature for 10-15 minutes, and then cooling to room temperature to obtain the surface sizing solution.

4. The method for preparing digital thermal transfer paper with low waste rate according to claim 1, characterized in that: The preparation method of the slurry sizing solution is: 100-150 parts by weight of water and 8-15 parts by weight of cationic starch are stirred and mixed at 300-500 rpm for 20-30 minutes, heated to 85-90° C., kept warm for 15-20 minutes, and then cooled to room temperature to obtain the slurry sizing solution.

5. The method for preparing digital thermal transfer paper with low waste rate as claimed in claim 1, characterized in that: The preparation method of the modified sizing agent comprises the following steps, measured in parts by weight: S1: Add 15-35 parts of N,N-dimethylformamide, 2-5 parts of sizing agent and 1-3 parts of sodium hydroxide, stir and mix at room temperature for 1-4 hours, then add 0.001-1 parts of 4-dimethylaminopyridine and 1-6 parts of grafting agent, keep stirring at 30-75°C for 2-5 hours; S2: Filter the substance obtained in step S1 to obtain a filter cake, wash it with a 70-90 wt % ethanol aqueous solution for 1-3 times, dry it at 50-65° C. for 1-4 hours, and cool it to room temperature to obtain a modified sizing agent.

6. The method for preparing digital thermal transfer paper with low waste rate as claimed in claim 5, characterized in that: The sizing agent is any one of hydrogenated rosin glycerol ester, sodium alginate and carboxymethyl chitosan.

7. The method for preparing digital thermal transfer paper with low waste rate as claimed in claim 6, characterized in that: The grafting agent is any one of monomethyl malonate, 3-methoxy-2-methyl-3-oxopropionic acid, and 3-[(tert-butoxycarbonyl)sulfanyl]propionic acid.

8. The method for preparing digital thermal transfer paper with low waste rate as claimed in claim 6, characterized in that: The grafting agent is 3-[(tert-butoxycarbonyl)sulfanyl]propionic acid.

9. The method for preparing digital thermal transfer paper with low waste rate as claimed in claim 1, characterized in that: In the step 5, the metering rod is 20-50S, the surface glue liquid is applied on the front side, the viscosity of which is 10-40mPa.s and the solid content is 8-15%; the back side is coated with a coating glue liquid, the viscosity of which is 350-500mPa.s and the solid content is 30-50%.

10. A digital thermal transfer paper with low waste rate, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Production method of high stiffness heat transfer raw paper

    CN103726396A

  • Method for producing light coating digital heat transfer paper

    CN106758536A

  • Composite coating for tipping paper and manufacturing process thereof

    CN116180497A

  • Regenerated digital transfer printing body paper and production process thereof

    CN118422522A

  • Neutral sizing agent for paper making and method for sizing paper using the agent

    JP2001254291A

Cited By

  • Efficient production method of digital heat transfer paper

    CN119266018A